Voltamperometría: fundamentos electroquímicos y aplicaciones - González-Hernández, Jerson (2024)
Voltammetry is an electrochemical technique with a wide field of application in quantitative determinations of analytes, characterization analysis, and the study of diffusion, adsorption, reduction, and oxidation processes. The versatility of this analytical tool is due to the implementation of different modifications to the methodology based on technological advances that have improved equipment and the three-electrode systems, mainly. This review addresses the fundamental principles of voltammetry, which includes instrumentation, thermodynamics, and the kinetics of electrochemical processes, as well as a review of voltammetric techniques and some relevant applications in different fields such as environmental analysis, pharmaceutical industry, and forensic sciences. The multiple interdisciplinary studies based on voltammetry show a significant use and recognized applicability of this electrochemical technique.